Diplomasi Komersial Indonesia dalam Menarik Investasi Dari Korea Selatan Pada Industri Kendaraan Listrik - Syafitra, Vebyan; Afriani Sinulingga, Anita; Anggraini Austin, Diah (Palito, 2025)
Diplomacy is an important instrument in advancing the Indonesian economy, one of which is by attracting foreign investment. Indonesia's efforts to develop the electric vehicle industry can be realized because of Indonesia's success in attracting investment in the electric vehicle industry from South Korea. This study uses the concept of commercial diplomacy from Olivier Naray and Michael Kostecki. Descriptive qualitative approach and literature study data collection techniques that use secondary data. This study aims to describe the commercial diplomacy by Indonesia in attracting investment from South Korea through main and supporting activities. The main activity in this research is the promotion of FDI. This is due to the efforts of the Indonesian government to attract investment from South Korea following the main activities of promoting FDI which is indicated by the Indonesian government conducting investment promotions by conducting seminars on investment opportunities and conducting industry-related investment agreements. In supporting activities the Indonesian government provides information on holding business forums and business networks, as well as getting involved in signing investment agreements and supporting foreign investors with the laws that apply in Indonesia in the electric vehicle industry.